Geometric parameters measurement for the cooling holes of turbine blade based on microscopic image sequence topographical reconstruction. (31st March 2023) - Li, Lei; Li, Bing; Zhang, Ruting; Xue, Zhangfeng; Wei, Xiang; Chen, Lei
Highlights: A measurement method for cooling holes based on microscopic image sequence topographical reconstruction is presented. A new focus evaluation operator is established to measure the focus of the image sequence of cooling holes. A new method based on normal distribution three σ principle adaptive fitting algorithm is used to search for the best extremum. The 3D topography of realistic cooling hole samples was acquired, and its geometrical characteristics were analyzed. Abstract: The accurate analysis of the geometric parameters of the cooling holes is essential for evaluating the processing quality of the holes. However, due to the complicated structure of cooling holes, typical measuring techniques suffer from low precision, low efficiency and high cost. With the microscopic image sequence topographical reconstruction, the three-dimensional (3D) topography of realistic cooling hole samples was acquired, and its geometrical characteristics were analyzed. This work presents a focus measure operator and an adaptive window fitting approach to recovering cooling hole topography well. Compared to the standard model obtained by X-ray microscopy, the standard deviation of the profile error is less than 0.018 mm; The measured geometric parameters are nearly identical to the standard value. The results validate the precision and efficacy of the proposed method, which has the potential to replace alternative techniques for determining the geometrical parameters of cooling holes.